2007
DOI: 10.1111/j.1471-0307.2007.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of processing parameters for the ultrasonic extraction of goat kid rennet

Abstract: Using abomasums of 2‐ to 3‐week‐old goat kids as material, the effects of some factors such as ultrasound intensity, extraction time, NaCl concentration in extraction solution and ratio of abomasums mucosa to extraction solution on the extraction yield of goat kid rennet were investigated. On the basis of single factor experiments, the processing parameters for ultrasound extraction were optimized using a four‐factor orthogonal and rotatory combinatorial design. The results showed that the optimum processing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Kim and Zayas (1991) introduced an ultrasound‐assisted procedure for abomasal tissue extraction; chymosin activity in such extracts was higher than in conventional extracts, and no effects on proteolytic activity nor on storage stability were observed. After optimising ultrasound extraction of kid abomasa Zhang and Wang (2007) observed a significantly faster enzyme transfer and increased enzyme yield.…”
Section: Chemistry and Production Technologymentioning
confidence: 94%
See 1 more Smart Citation
“…Kim and Zayas (1991) introduced an ultrasound‐assisted procedure for abomasal tissue extraction; chymosin activity in such extracts was higher than in conventional extracts, and no effects on proteolytic activity nor on storage stability were observed. After optimising ultrasound extraction of kid abomasa Zhang and Wang (2007) observed a significantly faster enzyme transfer and increased enzyme yield.…”
Section: Chemistry and Production Technologymentioning
confidence: 94%
“…2006; Moschopoulou et al. 2006; Zhang and Wang 2007). Kid chymosin has a molecular weight of approximately 36 kDa, a maximum milk clotting activity at 30°C and pH 5.5 and a remarkably higher thermostability (up to 55°C) than calf chymosin (Kumar et al.…”
Section: Chemistry and Production Technologymentioning
confidence: 99%
“…Anifantakis and Green [175] experimented by changing solutions four times on the same tissue in four days and reported that most enzymes are extracted in the first 24 h, and the rennet is most stable at a pH value of 5.5. The use of ultrasound resulted in an increase in activity and a yield of chymosin with a significantly shorter extraction time (80 min) [182][183][184]. The crude extract is then activated by lowering the pH to around 2.0 for a certain amount of time.…”
Section: Rennet Production Methodsmentioning
confidence: 99%
“…Thus, various clotting agents are important as substitutes for calf rennet, but these sources are not suitable for quality cheese production since they produce extremely bitter tastes (Neelakanta et al, 1999;Walsh and Li (2000); Kumar et al, 2006) Recombinant chymosin can also be used to produce cheese, but its use may be limited for consumer concern regarding genetically engineered foods (Egito et al, 2007). As animal clotting agents, there are studies that prove the ability to use camel rennet (Boudjenah-Haroun et al, 2011;Boudjenah-Haroun et al, 2014;Hattem et al, 2017), goat rennet (Zhang and Wang, 2007) and chicken pepsin (Benyahia-Krid et al, 2016) for bovine milk coagulation.…”
Section: Optimization Of Flocculation and Clotting Time Of Camel Milk...mentioning
confidence: 99%